A study of the cloud security attacks and threats. Issue 4 (July 2021) - Sureshkumar, V; Baranidharan, B
Abstract: Cloud storage has become an essential computational model today, providing flexible, defective resistant resources and dramatically reducing costs. However, there are major obstacles to protection issues in the wider adoption market. The multiformity of the cloud and the multi-location storing of data exacerbate these problems. The major issues to be discussed in protection are secrecy, authenticity, honesty, availability and auditability. Enabling more customers to switch to the cloud environment would allow for safe data and transfers from the service provider. Intrusion Detection Mechanisms, Cryptographic Methodology and Electronic Forensic Software are some of the assurance that a trustful service provider will have for the recuperation and collection of digital proof of intrusion activities. This paper provides a survey into some of the prevalent challenges, risks and ways to resolve these challenges in cloud platforms. We also discussed major cloud storage service for data storage and protection model.